UMP Library implements Waste4Fine to promote payment mode of fines with plastic drinking bottles - Wan Nurulhuda, Wan Zakaria (2019)
In support of the on-going UI Greenmetric Programme, Universiti Malaysia Pahang (UMP) Library has embarked on a payment mode of fines dubbed Waste4Fine – via plastic drinking bottles and cans – and has implemented it beginning March 13, 2019.